Clinical Evaluation and Management of Household Cleaning Product Ingestions in a Pediatric Emergency Department - Aytac Goktug; Mehmet Muhsin Kefçi; Gülser Esen Besli; Çiğdem Ulukaya Durakbaşa (Türk Tıp Dergisi, 2026)
Objective: To evaluate the demographic, clinical, and prognostic characteristics of household cleaning product ingestion in a pediatric emergency department. Methods: This retrospective study evaluated pediatric patients admitted to the emergency department after ingesting household cleaning products. The ingested agents were categorized into high- and low-risk groups. Demographic profiles, prehospital interventions, clinical symptoms, physical examination findings, and endoscopic outcomes were analyzed to compare the clinical characteristics and outcomes between the risk groups. Results: The cohort predominantly consisted of children under five years of age (80.0%) and males (56.0%). Notably, 24.0% of cases involved inappropriate and harmful pre-hospital interventions by caregivers. At presentation, 64.0% of patients were asymptomatic. Consistent with this selective approach, we performed endoscopy in 11 patients, representing 50.0% of the high-risk group, all of whom had presenting symptoms, abnormal physical examination findings, or both symptoms and findings. No patient in the low-risk group underwent endoscopy (p